Long-term lead and mortality following pacemaker and defibrillator implantation in adult congenital heart disease. (3rd October 2022) - Stokes, A; Karadakhy, O; Lui, C; Argyriou, A; Almansoor, Z; Adegboye, O; Biswas, S; Raj Krishna, G; Agrawal, D; Shah, A; Kirkwood, G; Morris, G
Abstract: Background: Adult congenital heart disease (ACHD) survival has dramatically improved in recent decades. As such, clinicians now face the complex long-term interactions of congenital and chronic heart diseases. One area of continuing mortality in this group is arrhythmias, especially in those with cardiovascular implantable electronic devices (CIEDs). With these developments in survival, the long-term outcomes of the CIED systems and their effects on mortality are beginning to be elucidated. Aims: This study aims to compare the effects of system location, surgical history, patient demographics and congenital disease complexity on lead survival, complication distributions and patient mortality in ACHD CIED patients. Methods: A retrospective cohort of 250 ACHD CIED patients with follow up at a heart centre was collated from clinical correspondence letters and CEID records. Data was collected on demographics, mortality and lead survival and complications. Survival data was analysed with Kaplan-Meier (KM) curves and hazard ratio tests. Results: Complex ADHD patient survival was less than the non-complex cohort (HR 0.38, 95% CI 0.22–0.67, p<0.01). Lead survival was longer in non-surgical patients (HR 1.42, 95% CI 1.13–1.78, p<0.01) and longer in female patients (HR 1.35, 95% CI 1.07–1.69, p<0.01) (Figure 1). No significant differences in mortality or lead survival were seen between epicardial and transvenous systems. Conclusions: Complex ACHD is associated with worse patient mortality in CEID patients. Surgical history and male gender are associated with worsened lead survival. Funding Acknowledgement: Type of funding sources: None.